Accurel MP 1000 as a support for the immobilization of lipase from Burkholderia cepacia: Application to the kinetic resolution of myo-inositol derivatives. Issue 10 (October 2015) - Manoel, Evelin A.; Ribeiro, Marcela F.P.; dos Santos, Jose C.S.; Coelho, Maria Alice Z.; Simas, Alessandro B.C.; Fernandez-Lafuente, Roberto; Freire, Denise M.G.
Graphical abstract